Factors Affecting the Participation Rate of Young Farmers in the Sawangan Organic Farmers Association, Magelang Regency - Fatma Fauzia Fanani; Siwi Gayatri; Joko Mariyono (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
The Sawangan Organic Farmers Association (GATOS) is said to have many members but is dominated by old farmers, while members who are classified as young farmers are still less active in playing a role in group activities. It is necessary to analyze the factors that affect the problem. This study aims were to analyze the factors that influence the participation of young farmers in the GATOS Group in Sawangan District, Magelang Regency. The research was conducted in March – May 2022 and was located at the Sawangan Organic Farmers Association. The research is survey research with a sampling methods, namely purposive random sampling with a total of 56 young farmers. The study used primary data and secondary data. The data collection methods used were interviews, observations and documentation. The data analysis methods used were quantitative descriptive analysis methods and multiple linear regression analysis methods. The results of the analysis of this study shows that age, level of education, ability, opportunity and willingness simultaneously had an influence on the participation of young farmers in GATOS. Ability, opportunity and willingness partially affect the level of participation of young farmers in GATOS, meanwhile the age and level of education partially did not have a significant effect toward the participation rate of young farmers.